Pembuatan dan Karakterisasi Deoiled Spent Bleaching Clay (DSBC) terpilar TiO2 dengan penambahan surfaktan rarasaponin” - Nauval Dwi Fadillah; Noor Hindryawati; Aman Sentosa Panggabean (JURNAL KIMIA MULAWARMAN, 2017)
Synthesis and characterization TiO2 pillared deoiled spent bleaching clay (DSBC) with rarasaponin as surfactant has been conducted. The activation of DSBC was performed by H2SO4 1N . Characterization had been conducted use X-Ray Diffraction, Flourescent Diffraction, Fourier Transform Infared Spectroscopy and Scaning Electron Microscopy. The results showed cristalinity of TiO2 pillared deoiled spent bleaching clay had increase until 72,5014 % after calcined 500 oC and expected there is Ti on layer based on SEM analysisSynthesis and characterization TiO2 pillared deoiled spent bleaching clay (DSBC) with rarasaponin as surfactant has been conducted. The activation of DSBC was performed by H2SO4 1N . Characterization had been conducted use X-Ray Diffraction, Flourescent Diffraction, Fourier Transform Infared Spectroscopy and Scaning Electron Microscopy. The results showed cristalinity of TiO2 pillared deoiled spent bleaching clay had increase until 72,5014 % after calcined 500 oC and expected there is Ti on layer based on SEM analysisSynthesis and characterization TiO2 pillared deoiled spent bleaching clay (DSBC) with rarasaponin as surfactant has been conducted. The activation of DSBC was performed by H2SO4 1N . Characterization had been conducted use X-Ray Diffraction, Flourescent Diffraction, Fourier Transform Infared Spectroscopy and Scaning Electron Microscopy. The results showed cristalinity of TiO2 pillared deoiled spent bleaching clay had increase until 72,5014 % after calcined 500 oC and expected there is Ti on layer based on SEM analysis.